Campylobacter jejuni Multilocus Sequence Types in Humans, Northwest England, 2003–2004 - Sopwith, Will (Centers for Disease Control and Prevention, 2006)
Detailed understanding of the epidemiology of Campylobacter is increasingly facilitated through use of universal and reproducible techniques for accurate strain differentiation and subtyping. Multilocus sequence typing (MLST) enables discriminatory subtyping and grouping of isolate types into genetically related clonal complexes; it also has the advantage of ease of application and repeatability. Recent studies suggest that a measure of host association may be distinguishable with this system. We describe the first continuous population-based survey to investigate the potential of MLST to resolve questions of campylobacteriosis epidemiology. We demonstrate the ability of MLST to identify variations in the epidemiology of campylobacteriosis between distinct populations and describe the distribution of key subtypes of interest.